Prevalence of post-traumatic stress disorder in Peruvian military: a cross-sectional study - Valladares-Garrido, Mario J.; Picón-Reátegui, Cinthia Karina; Zila-Velasque, J. Pierre; Failoc-Rojas, Virgilio E.; Victorio, César Johan Pereira; Valladares-Garrido, Danai; Vera-Ponce, Víctor J. (Frontiers in Psychiatry, 2025)
IntroductionThe COVID-19 pandemic has led us to stay at home in order to mitigate the increase in contagion, which has modified military personnel’s work as they had to be on the front-line of the global fight. Post-traumatic stress disorder (PTSD) is a psychiatric condition that has become a challenge for public health. Little research has been undertaken in military population, even less in the Latin American context. The objective is determining the prevalence and factors associated with post-traumatic stress disorder in military personnel in Lambayeque, Peru.MethodsThis is an analytic cross-sectional observational study in military staff that carried out first-line activities on the defense against COVID-19. The study population was comprised of 820 military personnel. To evaluate the factors associated with PTSD, we calculated prevalence ratios (PR) and confidence intervals at 95%, using simple and multiple regression models.ResultsThe prevalence of PTSD was 7.8% (95% CI: 5.8%–10.2%). The multiple regression model showed that smoking (PR: 2.84; 95% IC: 1.14-7.09), having worked between 13 and 18 months (PR: 2.62; 95% IC: 1.20-5.75), insomnia (PR: 4.09; 95% IC: 1.90-8.83), and fear of COVID (PR: 6.20; 95% IC: 2.70-14.22) were associated with a higher prevalence of PTSD in military personnel.ConclusionWe found that nearly one in ten military personnel presented PTSD. Factors associated with a higher prevalence included longer service time, smoking, insomnia, and fear of COVID-19. Although resilience showed a protective trend in crude analyses, this association was not significant after adjustment.